The Antagonism in Commercial Training: Vocational and Liberal Education : The Development of the Commercial School of the Trade Guild Hall in Gotha (1817-1902) - Götzl, Mathias [Verfasser]; Ketschau, Thilo [Verfasser] (My University, 2016)
"The 'dual' form of vocational education and training, a present day form of German commercial education, that includes both companies and schools as learning sites, dates back to the years of 1817/18, starting with the involvement of Ernst Wilhelm Arnoldi in the Thuringian residential city of Gotha. Until today little is known about this important institution from the perspective of economic-educational historiography. The study serves as a basis for this contribution to bridge the gap. This article aims for a critical perspective on (theory-oriented) historiography on schooling. Its approach is to go beyond the descriptive-narrative approach that is prevailing in (economic-) educational historiography. Theories of organizational sociology serve as categorical matrices for systematic structural recordings (description) and an aggregating analysis (explication)." (authors' abstract; BIBB-Doku)
Keywords: S 6.4.1 Kaufleute; T 1.2 Historische Berufsbildungsforschung; I 2.1.1.4 Thüringen; Kaufmännischer Beruf; Berufsausbildung; Kaufmännische Bildung; Historiographie; Historische Berufsbildungsforschung; Schulgeschichte; Kaufmännische Berufsschule; Gotha